Método de malha grossa para solução numérica de problemas de blindagem de nêutrons em geometria unidimensional na formulação de ordenadas discretas com perspectivas a cálculos multidimensionais em geometria retangular - Libotte, Rafael Barbosa (2021)
In this dissertation, is proposed and developed a spectronodal deterministic coarse- mesh method in the discrete ordinates formulation (SN ), applied to neutron shielding problems, considering the energy multigroup theory. For the one-dimensional geometry cases, the Modified Spectral Deterministic (MSD) methods equations were developed considering an arbitrary order scattering (L < N), which generates free of truncation error results. After analysing the results for the one-dimensional problems, we invested in the perspective of extending this study in simulations involving bidimensional rectangular cartesian geometry problems. In this case, it is used a constant approximation in the transverse neutron leakage terms, which justifies the denomination MSD-CN, as, Modified Spectral Deterministic-Constant Nodal. Numerical results of some model-problems are presented, comparing the precision of the results generated and the CPU time (only in the 1D cases) with traditional methods found in the scientific literature. The numerical results for the solution of one-dimensional geometry problems were generated using the language JAVA and for the bidimensional geometry problems was used the language C++.